Zinc particles coated with bismuth oxide based glasses as anode material for zinc air batteries with improved electrical rechargeability. (10th January 2018) - Schmid, M.; Willert-Porada, M.
Abstract: Zinc particles are commonly used as anode material in primary zinc air batteries. One of the reasons for irreversibility of this battery system is degradation of zinc metal, such as zinc passivation by formation of ZnO layers in alkaline solution. A promising approach for reducing zinc degradation is modification of zinc with protective coatings. But up to now, no electrical rechargeability of coated zinc particles could be enabled after complete discharge. In this work, bismuth oxide based coatings are introduced which should improve cyclic stability. Bi2 O3 -ZnO-CaO and Bi2 O3 -ZnO-SiO2 glasses were prepared and their chemical stability as well as swellability in 6 M KOH were discussed. The coating of zinc particles was realized by mechanical method. The electrochemical performance of coated zinc particles was investigated by applying complete discharge and charge steps, and compared with the behavior of uncoated zinc particles. The results pointed out, that Bi2 O3 -ZnO-CaO-coated zinc particles enabled improved rechargeability. A cyclic stability of 20 full cycles was realized in excess electrolyte, whereas uncoated zinc achieved just one complete discharge. The cumulated zinc utilization of coated zinc particles could be improved to 465%, as compared to uncoated zinc showing just 85% in test cells with electrolyte limitation. Highlights: Functionalized zinc particles for rechargeable zinc air batteries. Coating of zinc particles with bismuth oxide based glasses. Zinc degradation was reduced by the coating forming an interpenetrating network. Cumulated zinc utilization could be increased up to 465% (uncoated zinc: 85%).